ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN SUSU SAPI PASTEURISASI DI KOPERASI PRODUKSI SUSU (KPS) BOGOR - Bella Yunita; Achmad Tjachja Nugraha; Acep Muhib (Departement of Agribusiness Faculty of Science and Technology, 2018)
This study aims to (1) find out the characteristics of consumers who consume pasteurized milk, (2) determine the factors that affect the level of demand for pasteurized milk and analyze the influence of these factors on the demand for pasteurized milk, and (3) analyze the elasticity of demand for pasteurized milk. The research was conducted at the Dairy Cooperative Production (KPS, North Bogor). A total of 100 respondents were interviewed by using purposive sampling techniques. Multiple regression analysis and analysis of demand elasticity through programs of Microsoft Office Excel 2007 and SPSS 21 were employed to analyze the data. The results showed that incomes, number of family members, ages, educations, and tastes jointly significantly affect demand for pasteurized milk at KPS Bogor with confidence level of 75 %. The result from short-term elasticities showed that those five variables were inelastics.